2003
DOI: 10.1530/eje.0.1490455
|View full text |Cite
|
Sign up to set email alerts
|

Functional in vitro studies on the role and regulation of interleukin-6 in human somatotroph pituitary adenomas

Abstract: Objective: Interleukin-6 (IL-6), a member of the gp130 cytokine family, is considered to be an important modulator of function and growth in endocrine anterior pituitary cells. In pituitary adenomas, where IL-6 is often produced by the tumour cells, it is thought to be involved in pituitary adenoma pathophysiology via autocrine/paracrine mechanisms. Methods: We have studied in primary cell cultures of human somatotroph adenomas whether IL-6 stimulates growth hormone secretion and whether intratumoral IL-6 is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…After incubating GH3 cells with IL-6 for 4 h, we observed that GH release was significantly enhanced by 10 2 -10 4 U/ml IL-6. In accordance with our findings, Mainardi et al (2002) and Thiele et al (2003) also demonstrated that IL-6 significantly stimulated GH release from the primary cultured human somatotrope pituitary adenomas and pig pituitary cells. The GH-stimulatory potency of IL-6 was identical to, or even stronger than that of GHRH in comparative studies performed by Thiele et al (2003).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…After incubating GH3 cells with IL-6 for 4 h, we observed that GH release was significantly enhanced by 10 2 -10 4 U/ml IL-6. In accordance with our findings, Mainardi et al (2002) and Thiele et al (2003) also demonstrated that IL-6 significantly stimulated GH release from the primary cultured human somatotrope pituitary adenomas and pig pituitary cells. The GH-stimulatory potency of IL-6 was identical to, or even stronger than that of GHRH in comparative studies performed by Thiele et al (2003).…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with our findings, Mainardi et al (2002) and Thiele et al (2003) also demonstrated that IL-6 significantly stimulated GH release from the primary cultured human somatotrope pituitary adenomas and pig pituitary cells. The GH-stimulatory potency of IL-6 was identical to, or even stronger than that of GHRH in comparative studies performed by Thiele et al (2003). Reduced expression of the cytokine transducer gp130, which is required for IL-6 signal transduction, by stably transfecting gp130 antisense into GH3 cells, inhibited IL-6-induced GH secretion and cell growth (Castro et al 2003).…”
Section: Discussionsupporting
confidence: 92%
“…IL-6 stimulates the release of ACTH from AtT-20 cells and enhances its release from rat hemipituitary glands. IL-6 also stimulates both ACTH secretion and proopiomelanocortin gene expression in corticotrophic adenoma cell cultures [55], and stimulates GH secretion in somatotrophinomas [56]. Furthermore, IL-6 stimulates the release of PRL, GH and LH from dispersed cell cultures of normal rat pituitary cells [reviewed in [57]] and GH release from rat hemipituitary glands [54].…”
Section: Relevant Cytokines In the Anterior Pituitarymentioning
confidence: 99%
“…In pituitary adenomas, constitutively produced intratumoural IL-6 contributes to the excessive hormone secretion in endocrine-active tumours via autocrine and paracrine stimulation of the IL-6 receptor (Thiele et al 2003). This results in tumour expansion by concomitantly stimulating tumour cell proliferation and tumour neovascularisation (Renner et al 2009).…”
Section: Pituitary Carcinomamentioning
confidence: 99%